Spanish phonetics and phonology in contact studies from Africa, the Americas, and Spain - Rao, Rajiv, 1979- (Issues in Hispanic and Lusophone linguistics ;, 2020)
"Spanish Phonetics and Phonology in Contact: Studies from Africa, the Americas, and Spain brings together scholars working on a wide range of aspects of the Spanish sound system and how their coexistence with another language in speech communities across the Hispanophone world influences their manifestation. Drawing upon seminal works in the fields of language contact in general, Spanish in contact with indigenous and regional languages, and laboratory approaches tied to the languages in question, the volume's contents employ acoustic and quantitative approaches, as well as both controlled and spontaneous data elicitation procedures, to shed light on how linguistic, historical, and social variables drive contact phenomena, and in turn, shape specific varieties of Spanish. It will pique the interest of researchers and students of fields such as contact linguistics, language variation and change, segmental and suprasegmental phonetics and phonology, and sociolinguistics"--